Origin of barite mineralization in the doğanşehir (Malatya): Trace and rare earth element, isotope and fluid inclusion evidence - Kara, Hatice; Bal Akkoca, Dicle (TUBITAK, 2021)
This study the main objective presented the geochemical and isotopic characteristics of the barite mineralization at the Doğanşehir (Malatya), located in the Eastern Taurids. These mineralizations observed are included in crack zones of metamorphic rocks. Trace element data of barite in the study area show that Ba, Pb and Zn may have been derived from different sources: these elements come from recrystallized limestones and siliceous rocks. The trends of the REE and the plots of the values of barites on the CeN/SmN versus CeN/YbN diagram indicate that seawater dominated the hydrothermal fluid depositing the barite and supplied the barium and sulfate ions, while a fluid mixture of seawater. Pb isotope studies (206Pb/204Pb=17.04-19.2;207Pb/204Pb=14.33-17.00 and208Pb/204Pb=34.19-41.66) indicate that the lead in barite was derived from the mantle, orogen, and crust and was slightly contaminated by the basement rocks. Sulfur isotopic studies indicate that the sulfur in barite has been derived from seawater sulfate sources (?34SVCDT values range from 17.5 ‰ to 30.7 ‰). Microthermometric studies on barite samples range from 85°C to 122°C, with an average of 110°C. Salinities vary from 0.2 to 2.6 NaCl wt%. Homogenization temperatures of the studied fluid inclusions suggest which were probably formed in epithermal conditions. © 2021, TUBITAK. All rights reserved.
Doğanşehir (Malatya)’da ki barit cevherleşmelerinin kökeni: iz ve nadir toprak element, izotop ve sıvı kapanım bulguları
Keywords: Barite; Fluid inclusion; Lead isotope; Sulphur isotope